Propofol attenuates the adhesion of tumor and endothelial cells through inhibiting glycolysis in human umbilical vein endothelial cells - Qi Jie; Wu Qichao; Zhu Xuqin; Zhang Shan; Chen Xiangyuan; Chen Wankun; Sun Zhirong; Zhu Minmin; Miao Changhong (Acta Biochimica et Biophysica Sinica)
Abstract Propofol is one of the most commonly used intravenous anesthetics and plays an important role in tumor suppression. In the present study, we aimed to investigate the mechanism by which propofol attenuates tumor endothelial cells (TECs) and tumor cell adhesion to inhibit tumor metastasis in vitro. Human umbilical vein endothelial cells (HUVECs) cultured in Dulbecco’s modified Eagle’s medium were treated with tumor conditioned medium for 24 h, followed by 4 h of treatment with or without 25 μM of propofol, 10 μM of KN93, 500 μM of MK801, or 20 μM of rapastinel. It was found that propofol inhibited TEC adhesion and the glycolysis level of TECs. Consistently, propofol inhibited the expressions of adhesion molecules (E-selectin, ICAM-1, and VCAM-1) and glycolysis proteins (GLUT1, HK2, and LDHA) in TECs. Moreover, propofol attenuated the expression of HIF-1α, the phosphorylation of AKT and Ca2+/calmodulin-dependent protein kinase II (CaMKII), and the Ca2+ concentration in TECs. MK801, an inhibitor of NMDA receptor, and KN93, an inhibitor of CaMKII, both inhibited the expressions of adhesion molecules and glycolysis proteins, in a manner similar to propofol. Additionally, rapastine, an activator of NMDA receptor, could counteract the effects of propofol. Our results indicated that propofol attenuates intracellular Ca2+ concentration, CaMKII and AKT phosphorylation, and HIF-1α expression, probably via inhibiting the NMDA receptor, thus inhibiting glycolysis and adhesion of tumor and endothelial cells.